2001
DOI: 10.1557/proc-703-v13.8
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of a Carbon Nanotube- Cyclodextrin Complex

Abstract: In this study the intermolecular interactions of small diameter (-0.7nm) carbon nanotubes and ycyclodextrin were examined. Four samples of y cyclodextrin and HiPco carbon nanotubes were prepared. The first, by grinding the tubes and the cyclodextrin (1:30 ratio) together in a dry mixture, the second was prepared in a similar fashion but was ground in the presence of water (lml). Finally an aqueous solution of y-cyclodextrin (0.3M) and HiPco carbon nanotubes (5mg) was prepared by refluxing for -100 hours, formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Instead it was suggested that the CD is absorbed at the surface of nanotube ropes by van der Waals forces and can cut the tubes 9 . Indeed initial evidence from spectroscopic studies did indicate that the γCD can be absorbed onto the surface of the tubes, however no evidence of cutting or opening the tubes was observed 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Instead it was suggested that the CD is absorbed at the surface of nanotube ropes by van der Waals forces and can cut the tubes 9 . Indeed initial evidence from spectroscopic studies did indicate that the γCD can be absorbed onto the surface of the tubes, however no evidence of cutting or opening the tubes was observed 13 .…”
Section: Introductionmentioning
confidence: 99%